Strengthening the World Bank's Role in Global Programs and Partnerships - Operations Evaluation Department (Washington, DC: World Bank, 2012)
This volume reports on a conference held by the World Bank's independent Operations Evaluation Department (OED) to discuss the Bank's rote in global program partnerships. The starting point for the discussions was a comprehensive review by OED of the effectiveness of 26 of the largest programs, including the Consultative Group on International AgricuRural Research and programs in health, environment, and trade. Participants at the conference provided crosscutting lessons about program design, implementation, and evaluation, and shared views about how the Bank can best help build commitment and assure financing for high priority global public goods that benefit the poor.